Rheological Property Changes in Polyacrylamide Aqueous Solution Flowed Through Microchannel Under Low Reynolds Number and High Shear Rate Conditions - Yishuai Li; Yukihiro Yonemoto; Yuki Yamahata; Akimaro Kawahara (Micromachines)
As an important structure of microfluidic devices, microchannels have the advantages of precise flow control and high reaction efficiency. This study investigates experimentally changing the rheological properties of a polyacrylamide (PAM) aqueous solution after flowing through a square microchannel with a hydraulic diameter of 0.5 mm under low Reynolds number and high shear rate conditions. To know the effect of the channel length on the change in viscosity and relaxation time, the length is changed to 100 mm and 200 mm. From the experiment, it is found that both the viscosity and relaxation time of the solution decrease with increasing the shear rate and the microchannel length. Based on the present experimental data, an empirical model is proposed to predict the change ratio of the relaxation time before and after passing through the microchannel, and the calculation with the model has an agreement with the experiment with root-mean-square absolute error of 0.007.